2005
DOI: 10.1063/1.2147847
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of a remarkable enhancement in the light emission from nanocrystalline porous silicon annealed in high-pressure water vapor

Abstract: To clarify the effect of surface passivation on the optical properties of nanocrystalline porous silicon (PS), the photoluminescence (PL) characteristics of PS have been investigated by employing a high-pressure water vapor annealing (HWA). PS samples with various porosities were prepared on (100)-oriented p-type (4Ωcm) single-crystalline silicon wafers by electrochemical anodization. Some samples were then electrochemically oxidized. The HWA treatment was then applied to the prepared PS samples at 0.5–3MPa an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
109
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(118 citation statements)
references
References 33 publications
9
109
0
Order By: Relevance
“…It was shown that the defect density at the Si/SiO 2 interface was very much reduced by HWA, resulting in reduced non-radiative recombination rates [9]. Furthermore, the SiO 2 network surrounding the Si nanocrystals is mostly unstrained and very uniform, resulting in very good stability of PS structure and PL [10]. The exciton localization in Si nanocrystals was also much enhanced [10].…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…It was shown that the defect density at the Si/SiO 2 interface was very much reduced by HWA, resulting in reduced non-radiative recombination rates [9]. Furthermore, the SiO 2 network surrounding the Si nanocrystals is mostly unstrained and very uniform, resulting in very good stability of PS structure and PL [10]. The exciton localization in Si nanocrystals was also much enhanced [10].…”
Section: Resultsmentioning
confidence: 95%
“…This high stability can be readily attributed to outstanding passivation of nanocrystalline silicon surfaces by high quality oxide as a result of HWA. The structure and the PL of HWA-treated PS have previously been studied [9,10]. It was shown that the defect density at the Si/SiO 2 interface was very much reduced by HWA, resulting in reduced non-radiative recombination rates [9].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gelloz et al prepared porous Si treated by high-pressure water vapor annealing [16][17][18][19][20] . Even though this method achieved a drastic enhancement in the PL efficiency, specialized and expensive equipment was required.…”
Section: Introductionmentioning
confidence: 99%